Internet connectivity disruption in Venezuela (Venezuela) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Venezuela. Data sourced from IODA.
Network Disruption Incident ID: VE-2026-0412. Severity: critical. Confidence: 67%